Multimarket Contact and Economic Performance - Scott, John T. (The Review of Economics and Statistics, 1982)
FOR the economy to work well, resources should flow freely from one industry to another in response to changing demands and costs. In textbooks, this process is via the capital market and entry and exit of firms. But entry can be by new firms or existing ones through diversification. Williamson (1970) and Weston (1970) stress advantages of internal capital transfers over the market.' Gort (1962, p. 4) and Rumelt (1974, p. 2) state multimarket operation of firms will speed redeployment of resources in response to profitable opportunities. They would be right if multimarket operation were not coincident with multimarket contact. While diversified companies may have advantages that would facilitate the movement of capital, they have enhanced opportunity for coordination if they meet in several markets. I term multimarket grouping the phenomenon of groups of diversified firms whose activities span to a significant extent the same markets. Multimarket grouping of sellers could reduce the flow of resources, thereby inhibiting a socially desirable competitive process, if it proceeded until mutual dependence among diversified sellers was recognized and reduction in competition coordinated, tacitly or otherwise. In short, where sellers have grown large through diversification, resources may not be efficiently reallocated among markets in response to changing conditions because interdependent groups of sellers recognize that reduces their profits. Even then, in a frictionless world, sellers other than those in the multimarket group could move resources into profitable areas. I reject such a frictionless world given evidence such as Mueller's (1977b) and the general theory of barriers to mobility (Caves and Porter, 1977). Those sellers having grown interdependent across markets are those who would have been most likely to enter given new profitable opportunities. Capacity expansion given such opportunities should be less rapid than if the multimarket interdependence did not exist. Is it in fact that just as with market concentration, not only the philosophy embodied in the Jeffersonian ideal, but economic efficiency provides grounds for concern about aggregate concentration when it coincides with multimarket grouping? This paper introduces methodology for measuring the significance of grouping and shows that when significant and coincident with high seller concentration, multimarket grouping does have economic implications. That coincidence, ceteris paribus, leads to higher profits. The question is whether those profits result from coordinated behavior or lower costs or both. The evidence suggests they are the result of economies of multimarket operation and barriers to the mobility of resources from outside the interdependent groups of sellers. Profits are lower for lines of business where multimarket contact is high but seller concentration is low, but higher when both contact and concentration are high than when concentration alone is high.